Logit Model of Computer-Based Data-Driven Creative Idea Generation in the Industry and Service Sectors - Hojjati, S. N.; Ghatari, A. R.; Alborzi, M.; Hassanzadeh, G. (Engineering, Technology & Applied Science Research, 2017)
Organizational creativity and employee idea generation have become important and essential elements of an organization’s success, as creativity results to increased performance. The need of increased creativity is evident in industrial and service companies. The main idea behind this paper is to analyze and demonstrate if accessing various types of data in certain ways and/or situations affects creative idea generation by the people involved in different industrial/service sectors, considering that now most of the employees use digital data. The current paper discusses how seven different factors are related to digital data affect creativity.